A new strain of docosahexaenoic acid producing microalga from Malaysian coastal waters - Manikan V.; Nazir M.Y.M.; Kalil M.S.; Kader A.J.A.; Yusoff W.M.W.; Hamid A.A.; Mohd Hafez Mohd Isa (Elsevier, 2024)
Indexed by Scopus/WOS